Pengembangan Media Pembelajaran Interaktif Menggunakan Google Slide pada Sekolah Swasta Alwashliyah Medan - Muhammad Syahrizal; Soeb Aripin; Dwina Priindini; Nola Dita Puspa; Tesa Aurelia Siregar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In the learning process in class, SD Alwashliyah 13 teachers can utilize a learning media that can improve students' creative and innovative mindsets. One of the learning media that can be used by teachers is the Google Slides application. This application can be used when the teacher presents or explains material to students in an attractive appearance and can make the class atmosphere active and enthusiastic. The current problem is that there are still many SD ALwashliyah 13 teachers who do not understand learning media in the form of Google Slides. So with community service at SD Alwashliyah 13 Medan with the theme of developing interactive learning media using Google Slides it is hoped that this dedication can become useful knowledge for SD Alwashliyah 13 teachers and aims to be more creative and innovative in making media tools learning during the learning process takes place.